High‐dose post‐transplant cyclophosphamide impairs γδ T‐cell reconstitution after haploidentical haematopoietic stem cell transplantation using low‐dose antithymocyte globulin and peripheral blood stem cell graft - Stocker, Nicolas (Clin Transl Immunology, 2020)
OBJECTIVES: Haploidentical haematopoietic cell transplantation (Haplo‐HCT) using peripheral blood stem cell (PBSC) grafts and post‐transplant cyclophosphamide (PTCy) is being increasingly used; however, data on immunological reconstitution (IR) are still scarce. METHODS: This retrospective study evaluated T‐cell immunological reconstitution in 106 adult patients who underwent allogeneic haematopoietic cell transplantation for haematologic malignancies between 2013 and 2016. RESULTS: At D30, while conventional T cells reached similar median counts in Haplo‐HCT recipients (n = 19) and controls (n = 87), γδ and Vδ2(+) T‐cell median counts were significantly lower in Haplo‐HCT recipients and it persists at least until D360 for Vδ2(+) T cells. PTCy induces a significant reduction in early γδ and Vδ2(+) T‐cell proliferation at D  7. At one year, the rate of increase in Epstein–Barr virus (EBV) viral load was significantly higher in Haplo‐HCT recipients as compared to controls (61% versus 34%, P = 0.02). In multivariate analysis, a higher γδ T‐cell count (> 4.63 μL(−1)) at D30 was the only independent parameter significantly associated with a reduced risk of increase in EBV viral load (RR 0.34; 95% CI, 0.15–0.76, P = 0.009). CONCLUSION: Immunological reconstitution of γδ T cells is significantly delayed after Haplo‐HCT using PTCy and low‐dose ATG and is associated with an increased risk of increase in EBV viral load.